2017
DOI: 10.1080/10400435.2017.1326413
|View full text |Cite
|
Sign up to set email alerts
|

Design and experimental evaluation of yoked hand-clutching for a lever drive chair

Abstract: Lever-drive wheelchairs lower physical strain but are less maneuverable than push-rim wheelchairs. Here, we study a possible solution in which the user simultaneously actuates clutches mounted between the levers and wheels each stroke via a clutch handle attached to one lever; this solution is of particular interest for user groups with only one functional hand. First, to demonstrate maneuverability, we show how this "yoked clutch" allows an experienced user to maneuver a constrained space. Then, we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Participants navigated a figure eight track with a 14 m long path designated with masking tape on the floor. This was an identical protocol to previous study with younger, unimpaired participants [12]. To match practice times with that previous study (in which participants completed a fixed number of laps each session rather than a fixed training duration like this study), participants practiced for the following number of minutes each session for six training days spaced over two weeks: Session 1: 5 min 37 sec; Session 2: 4 min 22 sec; Session 3: 4 min 1 sec, Session 4: 3 min 42 sec; Session 5: 3 min 35 sec; Session 6: 3 min 21 sec.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants navigated a figure eight track with a 14 m long path designated with masking tape on the floor. This was an identical protocol to previous study with younger, unimpaired participants [12]. To match practice times with that previous study (in which participants completed a fixed number of laps each session rather than a fixed training duration like this study), participants practiced for the following number of minutes each session for six training days spaced over two weeks: Session 1: 5 min 37 sec; Session 2: 4 min 22 sec; Session 3: 4 min 1 sec, Session 4: 3 min 42 sec; Session 5: 3 min 35 sec; Session 6: 3 min 21 sec.…”
Section: Methodsmentioning
confidence: 99%
“…the first trial’s performance time and α is the learning rate [14]. This same equation was also fit to a previously collected dataset acquired from young, unimpaired adults (mean age = 22.3 ± 2.8 years, N = 11) who drove the same version of LARA with the same experimental protocol [12]. Statistical comparisons were carried out with the Friedman’s test, Wilcoxon Rank Sum (WRKS) test and Wilcoxon Sign Rank (WSR) test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LARA (Lever-Actuated Rehabilitation and Ambulation) is a bimanual lever-driven wheelchair configured so that the paretic arm contributes to propulsion. 8,13 Pilot testing with a precursor device called RAE (the Resonating Arm Exerciser), which utilized the same lever configuration as LARA, showed that individuals with severe arm impairment in the chronic stage of stroke can pump a lever attached to the wheels of a wheelchair with their hemiparetic arm, rolling forward and backward, and that repeated pumping of these levers leads to therapeutic benefit. 14 We tested RAE in a home-based randomized control trial where independent training with RAE (~500 repetitions per hour) was found to be feasible and to significantly reduce arm impairment in individuals with chronic stroke, without increasing pain or tone.…”
Section: Introductionmentioning
confidence: 99%